ANALYZING AND IMPLEMENTING AN IN-HOUSE CLINIC MANAGEMENT SYSTEM FOR PT. XYZ - Alvian Radius Christianto; Ronny Juwono (IT for Society, 2021)
As one of the largest manufacturing company in Indonesia, PT. XYZ employs thousands of workers and staff, this has led to PT. XYZ is responsible for organizing and recording these thousands of workers and staff from PT. XYZ. Therefore, the In-House clinic of PT. XYZ must have all medical facilities requested by PT. XYZ to monitor the health of its workers. Therefore, a good management must be implemented to record and report all medical activities. This thesis will discuss the development of a Medical Management System to manage several aspects of a medical activity and follow the business needs of the PT. XYZ. Some aspects that will be regulated by this system management are: medical activity records, medical result documents, and data reports. This Management System will help PT. XYZ from the aspects already mentioned.